La mirada estudiantil acerca de la motivación por aprender: el derecho a una educación de calidad - Barrantes Pereira, Rolando (2022)
This article is based on research carried out at the Institute for Interdisciplinary Studies of Children and Adolescents (INEINA) of the Universidad Nacional in Costa Rica, entitled “Factors that affect the motivation to learn”. The main objective is to determine what are the factors that generate motivation in students so that a significant learning process is achieved; with the purpose of helping in the construction of proposals for a better approach by educational agents to the situations that occur in secondary education and that derive in conditions and actions that guarantee the right to quality education and keep adolescents away of exclusion and social inequalities. The present paper summarizes the results of the perspective of the students of one public and one private institution in the province of Heredia. The research approach was qualitative, descriptive in nature, in order to obtain the perspectives of the participants. The instrument for data collection was a questionnaire consisting of 14 open questions. The main results refer to the desire of the students to be recognized as people by the educational staff, seeking a connection between their characteristics and personal experiences and the interactions and pedagogical activities in the classroom. The importance of diversifying and innovating learning methodologies and strategies is mentioned, as well as the constant improvement of infrastructure and institutional services to promote motivation to learn and, therefore, guarantee the right to quality education.